Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.jaap.2006.12.015
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of developments in the pyrolysis of automotive shredder residue

Abstract: Worldwide, automotive shredder residue (ASR) is considered an increasingly problematic mixture of materials that needs the development of a processing solution.Pyrolysis is a process that has many advantages to offer, but despite many studies and developments in recent years at various levels of commercialisation, it is still generally considered unproven for this purpose. This paper critically considers developmental work published in the field, presents new results, and suggests that a major reason for the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 40 publications
3
34
0
1
Order By: Relevance
“…The rubber contents, mostly from hoses, ranged from 8% to 23%. The fines fraction was 7% by weight and supported Harder and Forton's (2007) study that this was difficult to break down into quantifiable materials.…”
Section: Commercial Assessment Of the Thermal Technologiessupporting
confidence: 61%
“…The rubber contents, mostly from hoses, ranged from 8% to 23%. The fines fraction was 7% by weight and supported Harder and Forton's (2007) study that this was difficult to break down into quantifiable materials.…”
Section: Commercial Assessment Of the Thermal Technologiessupporting
confidence: 61%
“…Harder and Forton, 2007 [35], Vermeulen et al 2011 [1] and Cossu et al 2014 [36], in their comprehensive review concluded that the use of ASR pilot-scale pyrolysis experiments were limited. The majority of testing being undertaken at lab-scale (mg-g hr -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present paper will critically review all aspects of reuse, recycling and recovery of ELV components and materials, to complement existing papers that only address parts of these issues [11,[17][18][19][20], and it will concentrate on post shredder technologies in which ASR is separated in different fractions in view of a more efficient recycling and energy recovery. The separation of metals is not considered in detail since reuse and recycling of metals is already well established.…”
Section: Introduction: the Broad Problem Of Elvsmentioning
confidence: 99%